Tawaduk Santri In Nusantara Cultural Perspective: A Multi-Discourse Analysis - Khotimah, Khusnul; Lutfitasari, Wevi; Taembo, Maulid; Hipni, Mohammad (UIN Maulana Malik Ibrahim Malang, 2024)
The pesantren tradition is a vital aspect of Nusantara culture that shapes students' humility in both religious and cultural practices. This humility (tawaduk) is expressed through distinct attitudes and activities. This study aims to present symbols of students' humility within Nusantara cultural practices and explore the ecological aspects of the unique pesantren culture as portrayed in mass media. This qualitative research utilizes a discourse analysis framework. In mass media discourse, symbols of students' humility are reflected in socio-cultural dimensions through cultural practices such as